Integrating inert dusts with other technologies in stored products protection. (2nd October 2021) - Ziaee, Masumeh; Ebadollahi, Asgar; Wakil, Waqas
Abstract: Inert dust insecticides (IDIs) can make a significant contribution to Integrated Pest Management (IPM) programs of stored grain providing insect control and preserving grain quality during storage. Unlike chemical-based insecticides, IDIs are unaffected by even high summer temperatures and maintain efficacy for many months rather than the days or weeks of their chemical counterparts. Their three main applications are structural treatment of empty storage facilities and grain- handling machinery; commodity capping and surface admixture treatments. For structural treatment, IDIs can be sprayed on surfaces as dust or aqueous slurry. IDIs can be applied along with aeration, temperature control and flow-through fumigation like phosphine or other gaseous insecticides in the form of capping treatments and in surface admixture treatments. IDI treated commodities have been approved by organic grower associations.